TAX AMNESTY: WHY IS IT BEHAVIOR COMPLIANCE? - Rahayu, Yayuk Ngesti (Jurnal Aplikasi Manajemen, 2019)
The main purpose of this paper is to discuss and describe the factors causing taxpayers not to comply with tax obligations in accordance with Law of the Republic of Indonesia Number 11 the Year 2016 regarding tax Amnesty, specifically taxpayers of Malang City, Batu City and Malang Regency. A total of 180 taxpayers who use the Tax Amnesty facility as respondents with purposive sampling criteria, WarpPLS 6.0 as a means of analyzing the mediation test influence of taxpayer awareness of tax compliance with ransom mediation. The results show that tax awareness and ransom influence tax compliance, tax awareness affects ransom. Ransom as a partial mediation can increase the influence of awareness of taxpayer compliance using the tax amnesty facility.